ON THE CREATION OF A RESEARCH COMPETENCIES DEVELOPMENT MODEL FOR HIGHER EDUCATION PROGRAMS GRADUATES - E. V. Karavaeva; O. V. Vorobieva; V. P. Tyshkevich (Высшее образование в России)
The article addresses one of the most urgent issues of the development of higher education in the light of the challenges of the strategy of scientific and technological development of the Russian Federation and the National system of qualifications – the problem of implementing a systematic approach in the formation of research competencies of graduates. On the basis of the performed systematization and critical analysis the paper presents the main methodological principles of the model of formation of research competencies of graduates of higher education programs. The first part provides information on international experience in creating a framework of qualifications in the field of science and innovation, the European framework of researchers' qualifications. The article presents the results of the analysis of the current state of the issue concerning regulation of scientific and pedagogical sphere of activity in the Russian Federation, and then substantiates the need to form a Unified sectoral framework of qualifications in the field of research, development and education, including training of scientific personnel and shows its general structure. In conclusion, as an illustration, a fragment of the model of research competencies of graduates of higher education programs developed on the basis of the Unified sectoral framework of qualifications is demonstrated.